SOSIALISASI VISI DAN MISI PROGRAM STUDI MPAI KEPADA STAKEHOLDER SEBAGAI UPAYA PENINGKATAN SINERGI DAN DAYA SAING INSTITUSI - Khasanah, Uswatun; Hadi, Imam Anas; Yahriyah, Siti (Tahta Media Grup, 2024)
This community service program aimed to enhance stakeholders’ understanding, commitment, and institutional synergy through the dissemination of the Vision and Mission of the Master Program in Islamic Education (MPAI). The identified problem was the limited internalization of VMTS (Vision, Mission, Goals, and Strategies) in academic practices and the suboptimal involvement of stakeholders in strengthening institutional governance. The program employed a participatory-dialogical approach through presentations, interactive discussions, and Focus Group Discussions (FGDs) involving 52 participants, including lecturers, students, administrative staff, alumni, and graduate users. The results showed an increase in stakeholders’ understanding from 23 to 45 participants. Furthermore, 43 internal stakeholders expressed implementation commitment, and 6 out of 8 external stakeholders demonstrated readiness for strategic collaboration. These findings indicate that vision and mission dissemination contributes to strengthening quality culture, enhancing academic accountability, and expanding institutional partnerships. The program has strategic implications for improving institutional competitiveness through participatory and collaborative governance.